Physician and patient preferences for oral anticoagulation therapy decision-making in atrial fibrillation: Results from a national best-worst scaling survey in Turkey (PREF-AF) - Kılıçkesmez, Kadriye; Aras, Dursun; Değertekin, Muzaffer; Özer, Nagihan; Hacıbedel, B.; Helvacıoğlu, K.; Koç, U.; Ölmez, A.; Ergene, Oktay (Elsevier Science Inc., 2022)
Objectives Cost-utility modeling informs reimbursement decisions and is based on the premise that health outcome improvements can be expressed as disease-independent utility scores. Previous cost-utility analyses of anti-calcitonin gene-related peptide therapies expressed the utility gain as a function of monthly migraine days (MMDs). Exploring the presence of an additional treatment effect on utility after controlling for MMDs can be insightful. This post hoc analysis of the DELIVER clinical trial (NCT04418765) for the preventive treatment of migraine aims to communicate the impact of eptinezumab on health utility scores. Methods Utility scores were estimated using data from study visits at which the Migraine-Specific Quality of Life Questionnaire (MSQ) was completed. MSQ scores were then mapped to EQ-5D-3L using previously published algorithms. A linear mixed model evaluating the effect of eptinezumab compared to placebo using change from baseline at week 12 and 24, adjusted for MMDs, was generated, and a fixed intercept for each study arm was used to estimate if eptinezumab effected points compared to placebo beyond MMD reduction.
Keywords: PREF-AF; Decision-Making in Atrial Fibrillation; Oral Anticoagulation Therapy; Patient Preferences